Preface to the Discussion of the ORSA Guidelines - Churchman, C. West (Management Science, 1972)
The September 1971 issue of Operations Research contains an ORSA committee's report entitled “Guidelines for the Practice of Operations Research.” The issue also contains other material relating to a dispute concerning a specific operations research project. It occurred to me that members of The Institute of Management Sciences might well have an interest, not in the dispute, but in the Guidelines, since these are obviously closely related to the significance of the practice of applied management science. Many of the members of The Institute of Management Sciences over the years have had an intense interest in the meaning of “the scientific method” as it relates to management science, not only in the model building aspects of the science, but in the broader concerns which occur in applications.